Dampak Pengurangan Kapasitas Ruang Tunggu Keberangkatan terhadap Pergerakan Penumpang pada Masa New Normal di Bandar Udara Internasional Pattimura Ambon - Dogi, Juan Armando Padji; Perangin Angin, Andi Frianto (Politeknik Penerbangan Jayapura, 2023)
Ambon Pattimura International Airport is an airport that serves domestic and international flights. This airport always experiences an increase in passengers every year. Therefore, good service standards and guaranteed security are needed. When the author conducted research at Pattimura International Airport, Ambon, the author found problems in the field related to service standards at the passenger terminal, especially in the waiting area. The reason is the implementation of the new normal at the airport which requires the seat capacity in the waiting room to be reduced by fifty percent of the number of seats available so that there is the potential for crowds of passengers in the area and disrupt the smooth flow of passengers. So the author concludes the need for a review of service standards in the waiting room area. The research methodology uses descriptive qualitative research methods, namely by describing the current state of the object of research and by using a qualitative approach. Data were obtained from direct observations in the field, especially in the waiting room area of the gate waiting room at Pattimura International Airport, Ambon. The results of the research that the authors examine prove that a review and coordination between work units at the airport is still needed. This is done so that there is no accumulation of passengers in the gate waiting room area and provides a sense of comfort to airport service users.